The starvation hormone, fibroblast growth factor-21, extends lifespan in mice - Zhang, Yuan; Xie, Yang; Berglund, Eric D; Coate, Katie Colbert; He, Tian Teng; Katafuchi, Takeshi; Xiao, Guanghua; Potthoff, Matthew J; Wei, Wei; Wan, Yihong; Yu, Ruth T; Evans, Ronald M; et al. (eLife, 2012)
Fibroblast growth factor-21 (FGF21) is a hormone secreted by the liver during fasting that elicits diverse aspects of the adaptive starvation response. Among its effects, FGF21 induces hepatic fatty acid oxidation and ketogenesis, increases insulin sensitivity, blocks somatic growth and causes bone loss. Here we show that transgenic overexpression of FGF21 markedly extends lifespan in mice without reducing food intake or affecting markers of NAD+ metabolism or AMP kinase and mTOR signaling. Transcriptomic analysis suggests that FGF21 acts primarily by blunting the growth hormone/insulin-like growth factor-1 signaling pathway in liver. These findings raise the possibility that FGF21 can be used to extend lifespan in other species.
Keywords: longevity; fibroblast growth factor; growth hormone; liver; caloric restriction